Pertumbuhan Tanaman Kangkung Darat dengan Pemberian Mikroorganisme Lokal (MOL) Gamal (Gliricidia sepium) dan Limbah Ampas Kelapa - Jafar, Jusmiati; Syam, Asrullah; Kasmira, K (Journal Galung Tropika, 2023)
Gamal leaves and coconut dregs waste can be used as raw materials for making local microorganisms (MOL) through a fermentation process used as liquid organic fertilizer to support plant growth. This research aims to determine the effect of local microorganisms (MOL), Gamal, and coconut dregs on the growth of water spinach plants (Ipomoea reptans). This research uses a quantitative approach with an experimental research type using a Completely Randomized Design (CRD) method consisting of 4 treatments and 3 replications comprised of a control treatment, namely watering with water (K0), concentration 100 ml/L (K1), 150 ml/ L (K2), and 200 ml/L Water (K3). Data collection was obtained by measuring plant height, counting the number of leaves, weighing fresh weight, root length, secondary roots, and root volume. Data analysis was carried out using analysis of variance (ANOVA) at the ? level of 0.05. The results showed that the administration of local microorganisms (MOL) Gamal and coconut dregs with different concentrations significantly affected plant height, number of leaves, and fresh weight of land kale (Ipomoea reptans).